2016
DOI: 10.1007/s10495-016-1234-5
|View full text |Cite
|
Sign up to set email alerts
|

Berberine activates Nrf2 nuclear translocation and inhibits apoptosis induced by high glucose in renal tubular epithelial cells through a phosphatidylinositol 3-kinase/Akt-dependent mechanism

Abstract: Apoptosis of tubular epithelial cells is a major feature of diabetic kidney disease, and hyperglycemia triggers the generation of free radicals and oxidant stress in tubular cells. Berberine (BBR) is identified as a potential anti-diabetic herbal medicine due to its beneficial effects on insulin sensitivity, glucose metabolism and glycolysis. In this study, the underlying mechanisms involved in the protective effects of BBR on high glucose-induced apoptosis were explored using cultured renal tubular epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 49 publications
4
47
0
Order By: Relevance
“…BBR 20 mg/kg showed significant increase in Nrf2 expression in comparison to BBR 10 mg/kg. This increase in Nrf2 expression by BBR is similar to the previous studies . Although our study has demonstrated the beneficial effect of BBR in peripheral neuropathy, yet further studies are needed to explore the mechanism of BBR in the prevention of neuropathy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…BBR 20 mg/kg showed significant increase in Nrf2 expression in comparison to BBR 10 mg/kg. This increase in Nrf2 expression by BBR is similar to the previous studies . Although our study has demonstrated the beneficial effect of BBR in peripheral neuropathy, yet further studies are needed to explore the mechanism of BBR in the prevention of neuropathy.…”
Section: Discussionsupporting
confidence: 90%
“…Berberine (BBR) is an quaternary benzylisoquinoline alkaloid, derived from the Berberis species and has been used in Ayurveda and Chinese medicine for the treatment of various diseases . BBR, an activator of Nrf2, also has hypoglycemic, antitussive, antiplatelet, anti‐lipidemic and antioxidant effects …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6), suggesting that berberine is a strong Nrf2 activator. Previous studies also demonstrated the ability of berberine to activate Nrf2 nuclear translocation and promote its protective effects in different disease models (Zhang et al, 2016;Dinesh and Rasool, 2017;Mahmoud et al, 2017). These results suggest that the P-gp induction by berberine is achieved through activation of Nrf2.…”
Section: Discussionsupporting
confidence: 56%
“…Study finds the berberine functions as antioxidant through directly scavenging of ROS/RNS and suppression of ROS/RNS production [142]. Cells treated with berberine will induce expression of antioxidant related gene such as antioxidant defense (reduced-glutathione and superoxide dismutase) and oxidant-sensitive proteins (HO-1 and NRF2) [143]. …”
Section: Ros and Diseasesmentioning
confidence: 99%